Macroeconomic performance and external shocks on small, open economies : the Caribbean experience. - GAFAR, John (1996)
Discusses various types of external shocks, and presents some statistical estimates of the costs and benefits associated with external shocks. Argues that an outward-looking trade policy forces factor and commodity prices to reflect their scarcity values, and results in a more efficient allocation of resources